Hygienic Evaluation of Food for Schoolchildren in Educational Institutions (Eurasian Medical Research Periodical, 2024)
Eating is one of the important factors that determine the state of health, and it is an indicator of the health of each person and the entire population in general. Therefore, protecting the health of our people, along with a number of other activities, is aimed at organizing a full and rational diet of all groups of the population and with its help, ensuring the healthy growth and development of our children and maintaining their ability to work